2020
DOI: 10.1136/annrheumdis-2020-eular.2393
|View full text |Cite
|
Sign up to set email alerts
|

Op0050 adalimumab Introduction Versus Methotrexate Dose Escalation in Patients With Inadequately Controlled Psoriatic Arthritis: Results From Randomized Phase 4 Control Study

Abstract: Background:Methotrexate (MTX) is often used as first-line therapy for patients (pts) with psoriatic arthritis (PsA) despite limited efficacy and data on appropriate dosage. Minimal Disease Activity (MDA) is suggested as an optimal treat-to-target outcome. Biologic disease-modifying antirheumatic drugs (bDMARDs) have demonstrated improved outcomes (including MDA rates) over MTX. However, more data are needed to define the optimal timing of bDMARD initiation and characterize efficacy of MTX dose escalation, to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Seventeen trials were not included in the NMA either because they did not report results or did not report them at a time point of interest or because the dosing regimen during the randomised treatment phase was unclear. One further trial was considered for the NMA, but due to a lack of common comparator with other studies in the network it could not be included 35. Data from 46 unique RCTs were included in at least one NMA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen trials were not included in the NMA either because they did not report results or did not report them at a time point of interest or because the dosing regimen during the randomised treatment phase was unclear. One further trial was considered for the NMA, but due to a lack of common comparator with other studies in the network it could not be included 35. Data from 46 unique RCTs were included in at least one NMA.…”
Section: Resultsmentioning
confidence: 99%
“…Patient eligibility criteria across the included studies were largely consistent. Thirty-eight trials required patients to have been diagnosed with PsA for a minimum of 3 months,17–20 22 23 26 36–65 and 36 trials used CASPAR as PsA diagnostic criteria 17–20 22 24 26 35 37–40 42 45–57 60–62 64 66–69. All trials except for GO-DACT64 and MAXIMISE69 reported the number of swollen and tender joints required at baseline.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The NMA included 26 RCTs (20,23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) that assessed the ACR 50 outcome at 6-month follow-up.…”
Section: Resposta à Doença (Acr 50)mentioning
confidence: 99%